Informative providing in management of the tourist enterprises - Крамарчук, Світлана Петрівна; Смачило, Ірина Ігорівна (Technology audit and production reserves, 2014)
The influence of the information providing on management of the tourist enterprises is considered, as reformation changes of economy, sharpening and dynamics of competitive activity at the market of tourist services, information saturation cause the permanent changes of competition status of the tourist enterprises. It is proved the following needs of the tourist enterprises to optimize their performance: the creation of a database of tourism resources and tourism products in Ukraine; combining remote offices in a common network with a single base; application of marketing tools to promote national tourism product in Ukraine and in the world; participation in international tourism fairs and exhibitions to promote national tourism product; creation, positioning and brand promotion of tourism in Ukraine. It is proved that the proper information is necessary to optimize the potential tourist information flows. This will regulate the number of tourists that can simultaneously be within a certain area. The main econometric models such as linear, parabolic, polynomial ones are suggested to be used. It is highlighted the attention to the fact that the coefficients of econometric models need to be calculated and their credibility need to be assessed, using a system of normal equations or application software. The application for the adequacy of the econometric model to F-Fisher criterion is grounded. These models can be used for predicting tourist flows.